A New Approach to Predict Cyclic Response and Fracture of Shear Links and Eccentrically Braced Frames - Wen, Huajie; Mahmoud, Hussam (Frontiers in Built Environment, 2018)
In eccentrically braced frames subjected to large lateral demands, inelastic actions are mostly concentrated in shear links. The links vary in size and, when employed in frames, are known to be subjected to combined tension/compression and shear stress states that influence their strength, low-cycle fatigue behavior, and fracture characteristics. Despite their significance as the main energy dissipation elements in a structure subjected to seismic demand, simulating their full response, including the number of cycles to failure, of these links as individual components, or when employed in full frames, is lacking. This is primarily because until recently, most low-cycle fatigue models did not allow link failures under complex stress states to be captured. In this study, by means of a well-established ultra-low cycle fatigue criterion, the behavior of these links is fully assessed. The focus is on short shear links since they are widely used in comparison to intermediate or long links. Results of the simulations are compared with their experimental equivalents and excellent comparisons are achieved, confirming the validity of the simulation methodology and providing, for the first time, a framework for simulating the ultra-low cycle fatigue behavior of shear links. The verified response prediction methodology is then applied at the structural level, and nonlinear pushover analysis on eccentrically braced frames are conducted. Unlike existing numerical approaches where failure is indicated through a prescriptive target performance, such as 5% inter-story drift for collapse prevention, the pushover analysis is conducted until complete fracture of the links and failure of the system. Seismic design parameters, such as deign and elastic base shears as well as force reduction factors, are also determined based on the pushover curves. The results demonstrate that the proposed approach can reliably predict the performance of eccentrically braced frames and can potentially be used in future design and analysis of such frames.